Performance evaluation of 2-port MIMO LTE-U terminal antenna with user’s hand effect - Ahmed Mohamed Elshirkasi; Azremi Abdullah Al-Hadi; Rizwan Khan; Ping Jack Soh (Bulletin of Electrical Engineering and Informatics, 2019)
This paper presents the performance evaluation of 2-port MIMO antenna for LTE-U sub 6 GHz band. The evaluation focuses on the effect of user’s hand in a uniform environment and the analysis were carried out on simulation and measurement data of antenna ports. Results show that the highest performance of the design is on the frequency range from 4.5 GHz to 5.5 GHz, and the ports have low envelope correlation coefficient (ECC) less than 0.16 in both cases of without and with user’s hand. However, the presence of the user’s hand reduces mean effective gain (MEG) of ports and diversity combining gain by more than 1.6 dB compared with no-hand case. The multiplexing efficiency is around 81% and reduced by the presence of the user’s hand to 55%. Despite this reduction; the design shows high spatial multiplexing capability in both cases. The capacity carried by the second transmission eigenmode is about 39% from the total capacity under waterfilling algorithm transmit power allocation.